Visual Arts Audience Development In Saudi Arabia: A Case Study On Youth In Riyadh - Alnasser, Nada Saad (2024)
This study investigates audience development within the visual arts sector among Saudi youth, contextualized within the broader framework of the 2030 Saudi Vision. Initiated in 2016, this vision aspires to elevate the country's social, educational, economic, and cultural facets. Notably, this study underscores a critical gap in the existing strategies, pinpointing a lack of emphasis on audience development despite significant investments in artistic infrastructure and enterprise support.